Socioeconomic and Environmental Aspects of Traditional Firewood for Cooking on the Example of Rural and Peri-Urban Mexican Households - Guadalupe Pérez; Jorge M. Islas-Samperio; Genice K. Grande-Acosta; Fabio Manzini (Energies, 2022)
Firewood is a solid biofuel that is widely used for cooking in Mexico’s residential sector. This study seeks to identify relevant factors in firewood consumption patterns, and their implications for climate change, gender, and health, and for energy poverty in Mexico, by climate region and socioeconomic level. For this purpose, a statistical analysis was conducted of recently published official information. We estimate that a total of 31.3 million Mexicans—26% of the total population—use firewood, and we have identified three main types of users: (i) exclusive firewood users (30%); (ii) mixed firewood users using firewood as their primary fuel (18%) and (iii) mixed firewood users using firewood as their secondary fuel source (52%). Total consumption of firewood was estimated at 116.6 PJ, while estimated greenhouse gas emissions were 8.1 million tCO2e. Out of all the households studied, 53% were in the tropical climate region; 59% were categorized as being in the “low” socioeconomic level; and 75% were in population centers comprising fewer than 2500 inhabitants. Some 68% of households do not pay for the acquisition of firewood, and for those households that do pay for the resource, estimated transactions total USD 286.9 million. Expenditures on firewood for energy represent up to 10% of household income. Finally, it was estimated that 15.7 million direct users of firewood are women who use the resource in three-stone fires, in which they expose themselves to health risks in doing so. In conclusion, main universal findings, the study’s limitations, and future research are presented.